Manipulation of magnetic nanoparticles with rotating and pulsed magnetic field - Bodnar, Laszlo (Kansas State University, 2019)
In the bioengineering field, magnetic nanoparticles are investigated for a variety of reasons. Magnetic nanoparticles in combination with magnetic fields are used as drug carriers, MRI contrast agents and therapeutic agents for cancer treatment. This research requires the cooperation of several research groups from different fields and therefore, a portable magnetic field generating device is often required. In the first part of this thesis the construction of a pulsed magnetic field generating device is described. The instrument is portable, easy to use and the commercial production of it is feasible. The device is based on two Bitter-type electromagnets driven by a resonant circuit. The bore of the coils can accept a test tube or adherent cell culture tube. The planned experiments involve drug release experiments performed on 5(6)-Carboxyfluorescein containing liposomes and cell viability assays using adherent cell cultures treated with an antibiotic drug and magnetic nanoparticles. To generate the magnetic pulse, a capacitor is discharged via a spark-gap switch, triggered by a high-voltage trigger spark generator. The device is controlled by a programmable logic controller (PLC) and an Arduino unit. The profile of the magnetic field generated by the coils was obtained by placing a high resolution magnetic viewing film into the coils. In the second part of this thesis, the creation and testing of a rotating field hyperthermia device is described. A perpendicular coil pair was constructed and driven through a resonant circuit. Iron-oxide nanoparticles were used to investigate the heating efficiency of the system. Magnetic heating was observed, however, the resistive heating of the coil material and the radiative heat transfer from the coil to the sample make the temperature measurement results unreliable. A more sophisticated experimental setup is needed in which the cooling of the coils and the thermal insulation of the sample is possible. Based on our results we presume that, with the aforementioned issues addressed, rotating magnetic fields can be a better alternative to the widely used alternating magnetic fields.
Keywords: Magnetic field; Hyperthermia; Drug release; Nanoparticles; Method developement